PENERAPAN VALUE ENGINEERING PADA PROYEK PEMBANGUNAN KANTOR TANAMAN DAN TUK PG. KEBON AGUNG MALANG - Devi Zettyara, Wahiddin, Agnes Hanna Patty (Jurusan Teknik Sipil, Politeknik Negeri Malang, 2015)
Completed with the project price of IDR 10,750,900,000.00, the 4-floor office in the area of about 6,688 m2 is located on Jl. Raya Kebon Agung Malang. The existing beam was constructed using concrete beam. The objective of analysis is to make alternatives of beam work by employing Value Engineering (VE) analysis in order to find out the most efficient price. The three beam works to alternate the existing are (1) I section concrete beam, (2) T section concrete beam and (3) composite beam. The analysis started with a literature study in VE references, material cost, and beam work of the project. Next, the structure strength and cost of the existing beam was analyzed followed by the analyses of each alternatives. Finally, the structure strength and cost the existing beam and the alternatives were compared. The results of the study shows structurally the smaller sectional shape the smaller the value of øMn and Mu are produced. In term of cost, the alternative that has the greatest value of saving is alternative 2 or T-shaped concrete beam of 29.39%.Keywords: value engineering, cost saving, beam structure